2018
DOI: 10.3926/jotse.320
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the industrial PhD: Stakeholder insights

Abstract: Research and practice have called for a change in engineering education towards a more practice-oriented curricula to provide engineers with the skills they need for creating solutions for future challenges. While most studies address undergraduate programs, only little attention has been paid to graduate and post-graduate education. The Industrial PhD is expected to give PhD students on-the-job training to gain practically relevant and professional tacit knowledge and to enhance their set of soft skills. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In the coursework-based model typical in the USA, Russia and Sweden, such skill development can be introduced through courses and seminars along with supervisor-devised professional development plans aimed at making students better communicators within our diverse societies. The industrial PhD more common in northern Europe in the STEM disciplines, however, has made blending research and noncognitive skills within a three-year framework a priority (Grimm, 2018; Gustavsson et al , 2016). Although industrial PhDs consist of a close link to an outside company in a way that does not apply directly to many fields, such as the arts and humanities, academic PhD programs worldwide can adapt this approach to a wider range of employability skills without sacrificing research skills or lengthening the time to degree.…”
Section: Discussionmentioning
confidence: 99%
“…In the coursework-based model typical in the USA, Russia and Sweden, such skill development can be introduced through courses and seminars along with supervisor-devised professional development plans aimed at making students better communicators within our diverse societies. The industrial PhD more common in northern Europe in the STEM disciplines, however, has made blending research and noncognitive skills within a three-year framework a priority (Grimm, 2018; Gustavsson et al , 2016). Although industrial PhDs consist of a close link to an outside company in a way that does not apply directly to many fields, such as the arts and humanities, academic PhD programs worldwide can adapt this approach to a wider range of employability skills without sacrificing research skills or lengthening the time to degree.…”
Section: Discussionmentioning
confidence: 99%
“…The pan-European DOC-CAREERS study of collaborative programmes has identified a range of working practices and supporting policy measures, stressing the need for more knowledge on career pathways (Borrell-Damian et al, 2010). Collaboration is not always harmonious, as indicated by Grimm (2018) in her case study of a German programme with the automobile industry. A typical hybrid scheme is that for semi-industrial PhD students, who work in research centres with close industrial contacts (Granata and Dochy, 2016).…”
Section: Organizing Collaborative Phd Programmesmentioning
confidence: 99%
“…With the expansion of scope of the LIS field to information studies further increased the growth of docotoral studies. In [15] [16] [17] [18] highlights were given to the potential of doctoral studies for academics, researchers and practitioners. The peculiarities of the field, however, need to be taken into consideration in making a decision to start a doctoral program.…”
Section: Rationalementioning
confidence: 99%